Pengabdian Masyarakat melalui Konsultasi Persetujuan Bangunan Gedung (PBG) pada Pendirian Pabrik Pengolahan Kelapa Sawit PT. xx - Purwo Subekti; Bambang Edison; Anton Ariyanto; Taufik Kurniawan (FKULTAS TEKNIK, 2023)
Consultation for PBG approval for a permit to establish a Palm Oil Processing Factory PT. xx, conducted to provide recommendations for the issuance of PBG. The method for consulting on document inspection is a presentation and discussion related to the applicant's technical documents. Consultation community service activities include detailing the required documents for PBG applications and providing suggestions for improving the documents requested. Based on the results of the 1st consultation, it is known that the applicant has not completed the documents according to the applicable regulations, so further consultation is needed after the 1st consultation recommendations are corrected. The 2nd consultation activity resulted in an agreement that the applicant had completed the changes and complied with the technical plan document, and continued with the plenary to determine the recommendation for the issuance of PBG.